Chemoenzymatic Halocyclization of γ, δ‐Unsaturated Carboxylic Acids and Alcohols. Issue 1 (22nd October 2019) - Younes, Sabry H. H.; Tieves, Florian; Lan, Dongming; Wang, Yonghua; Süss, Philipp; Brundiek, Henrike; Wever, Ron; Hollmann, Frank
Abstract: A chemoenzymatic method for the halocyclization of unsaturated alcohols and acids by using the robust V‐dependent chloroperoxidase from Curvularia inaequalis ( Ci VCPO) as catalyst has been developed for the in situ generation of hypohalites. A broad range of halolactones and cyclic haloethers are formed with excellent performance of the biocatalyst. Abstract : You had me at "halo" : A chemoenzymatic method for the halocyclization of unsaturated alcohols and acids by using a robust V‐dependent chloroperoxidase as catalyst has been developed for the in situ generation of hypohalites. A broad range of halolactones and cyclic haloethers are formed with excellent biocatalyst performance.